The role of negatively charged lipids in lysosomal phospholipase A2 function - Abe, Akira (The American Society for Biochemistry and Molecular Biology, 2009)
Lysosomal phospholipase A2 (LPLA2) is characterized by increased activity toward zwitterionic phospholipid liposomes containing negatively charged lipids under acidic conditions. The effect of anionic lipids on LPLA2 activity was investigated. Mouse LPLA2 activity was assayed as C2-ceramide transacylation. Sulfatide incorporated into liposomes enhanced LPLA2 activity under acidic conditions and was weakened by NaCl or increased pH. Amiodarone, a cationic amphiphilic drug, reduced LPLA2 activity. LPLA2 exhibited esterase activity when p-nitro-phenylbutyrate (pNPB) was used as a substrate. Unlike the phospholipase A2 activity, the esterase activity was detected over wide pH range and not inhibited by NaCl or amiodarone. Presteady-state kinetics using pNPB were consistent with the formation of an acyl-enzyme intermediate. C2-ceramide was an acceptor for the acyl group of the acyl-enzyme but was not available as the acyl group acceptor when dispersed in liposomes containing amiodarone. Cosedimentation of LPLA2 with liposomes was enhanced in the presence of sulfatide and was reduced by raising NaCl, amiodarone, or pH in the reaction mixture. LPLA2 adsorption to negatively charged lipid membrane surfaces through an electrostatic attraction, therefore, enhances LPLA2 enzyme activity toward insoluble substrates. Thus, anionic lipids present within lipid membranes enhance the rate of phospholipid hydrolysis by LPLA2 at lipid-water interfaces.—Abe, A., and J. A. Shayman. The role of negatively charged lipids in lysosomal phospholipase A2 function.